2003
DOI: 10.1038/sj.gene.6364007
|View full text |Cite
|
Sign up to set email alerts
|

Testing the possible negative association of type 1 diabetes and atopic disease by analysis of the interleukin 4 receptor gene

Abstract: Variations in the interleukin 4 receptor A (IL4RA) gene have been reported to be associated with atopy, asthma, and allergy, which may occur less frequently in subjects with type 1 diabetes (T1D). Since atopy shows a humoral immune reactivity pattern, and T1D results from a cellular (T lymphocyte) response, we hypothesised that alleles predisposing to atopy could be protective for T1D and transmitted less often than the expected 50% from heterozygous parents to offspring with T1D. We genotyped seven exonic sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 36 publications
4
11
1
Order By: Relevance
“…This result is concordant with two independent family-based studies [10,12,14]. In the study of 309 US diabetic families, one nsSNP, rs1801275 (NP_000409/R576Q, deduced from the genotyping protocol of that study), was tested for type 1 diabetes association and no association was found [14].…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…This result is concordant with two independent family-based studies [10,12,14]. In the study of 309 US diabetic families, one nsSNP, rs1801275 (NP_000409/R576Q, deduced from the genotyping protocol of that study), was tested for type 1 diabetes association and no association was found [14].…”
Section: Resultssupporting
confidence: 81%
“…In the study of 309 US diabetic families, one nsSNP, rs1801275 (NP_000409/R576Q, deduced from the genotyping protocol of that study), was tested for type 1 diabetes association and no association was found [14]. In the other study [12], one promoter SNP and seven nsSNPs were tested in 3,475 families, with the two largest subsets being 999 UK families and 1,231 Finnish families. None of the nsSNPs in that study was significantly associated with type 1 diabetes in the total family subjects, but in the Finnish subset the nsSNP rs1805012 was associated with type 1 diabetes, with p=0.03 and odds ratio 0.77 (95% CI 0.62-0.97) [12].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations